PERLINDUNGAN KONSUMEN TERHADAP OBAT SIRUP YANG MEMILIKI IZIN EDAR MENGANDUNG ZAT BERBAHAYA - Windia Putri; Benni Rusli; Mahlil Adriaman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Drugs have a very important role in health services circulating among the community. Therefore, a supervisory role is needed for the Government and BPOM. Acoording to Law Number 80 of 2017 concerning the Drug and Food Control Agency. BPOM, in providing protection for consumers, of course, also pays attention to the procedures for drug distribution with the aim of avoiding irregularitas committed by unscrupulous business actors. With these problems, there are formulations of the problem including : 1. What is the process of drug supervision carried out by BPOM on the distribution of syrup drugs that already have distribution permits?, 2. What are the legal efforts taken by BPOM against business actors who are proven to have violated BPOM regulations?. This research method (empirical law research) is a legal research that examines that concept of law as real behavior (actual behavior), unwritten social phenomena experienced by everyone in obtaining legal protection. This study uses primary, secondary and tertiary data. The research results obtained are constumer protection against drug circulation before it is circulated and after it is circulated in accordance with the provisons. Legal efforts made by BPOM against business actor who commit violations, namely technical assistance and follow-up in the form of warning, stopping activities and revoking permits.